Computing the stability boundaries for the lagrange triangular solutions in the elliptic restricted three‐body problem - Prokopenya, A. N. (Mathematical Modelling and Analysis, 2006)
An algorithm is proposed for analytical computing the stability boundaries of the Lagrange triangular solutions in the elliptic restricted three‐body problem. It is based on the infinite determinant method. The algorithm has been implemented by using the computer algebra system Mathematica and the stability boundaries have been determined in the form of power series with respect to a small parameter with accuracy up to the 10th order. First Published Online: 14 Oct 2010